Mosquito species associated with horses in Madagascar: a review of their vector status with regard to the epidemiology of West Nile fever. Issue 1 (24th August 2021) - Tantely, M. L.; Guis, H.; Randriananjantenaina, I.; Raharinirina, M. R.; Velonirina, H. J.; Cardinale, E.; Raveloarijaona, N.; Cêtre‐Sossah, C.; Garros, C.; Girod, R.
Abstract: In Madagascar, the high West Nile virus (WNV) antibody prevalence reported in horse populations suggests a high level of vector‐horse contact. This study aims to characterize the mosquito species usually involved in WNV transmission in horse stables in Madagascar. Five horse stables were investigated in October and November 2016 in five distinct inland areas. Mosquitoes were collected using double net traps baited with human, poultry or horse as well as light traps. Blood meal identification from engorged females was performed using host‐specific PCRs. A total of 2898 adult mosquitoes were collected with Culex ( Culex ) antennatus (Becker) (40.7%), and Cx. ( Cux. ) quinquefasciatus Say (14.9%), being the most abundant species. The mosquito abundance varied between horse stables ( P  < 10 −7 ) and depending on the bait used in the double net traps ( P  < 0.003). Among the 190 tested blood meals, 119 consisted of single blood meals with 85 from horse, 17 from human, 16 from chicken, one from cattle and 71 consisted of mixed blood meals. The mosquito species collected during this study exhibited a generalist feeding behaviour allowing them to act as bridge vectors between different vertebrate hosts involved in WNV transmission cycle. Their vector status with regard to West Nile fever epidemiology is reviewed. Abstract : West Nile virus mosquito vectors diversity and abundance are different between urban, peri‐urban, rural and forest habitats, demonstrating important differences in the incidence of WNV between these habitats. Culex antennatus and Cx. quinquefasciatus may be important in WNV transmission in rural and urban areas, respectively. Both species and Cx. univittatus may play a role in peri‐urban area. These vectors are generalist feeders and may act as bridge vectors connecting birds with horses and humans, and WNV transmission cycle could be more complex than expected in forested area.